Dystrybucja jako instrument konkurowania przedsiębiorstw na rynku - Zawadzki, Piotr (Distribution as an instrument of enterprises' market competitiveness, 2005)
The article presents distribution as an instrument for enterprise’s competitiveness on the market. This instrument is not as effectively used by companies as eg. promotion, however, it can result in certain advantages for manufacturers. The author has presented characteristic features of basic forms of distribution channels giving specific consideration to conflicts within intermediary channels. The article defines determining factors for the choice of proper solution in order to reach the consumer most effectively, as well as illustrates different forms of distribution with regard to the degree of its intensity
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1095, s. 152-161